Does risk communication really decrease cooperation in climate change mitigation? - Giangiacomo Bravo; Mike Farjam; Olexandr Nikolaychuk (Friedrich Schiller University Jena, 2017)
Effective communication of risks involved in the climate change discussion is crucial and despite ambitious protection policies, the possibility of irreversible consequences actually occurring can only be diminished but never ruled out completely. We present a laboratory experiment that studies how residual risk of failure affects willingness to contribute to climate protection policies. Contrary to our initial hypothesis, we find that the contributions were higher in treatments with residual risk than in treatments without one. We interpret this as an outcome of a psychological process where residual risk puts participants into an "alarm mode", keeping their contributions high. We discuss the broad practical implications this might have on the real world communication of climate change.
Keywords: D71; Q54; H41; D80; 330; climate change mitigation; collective risk social dilemma; experiment; risk; voluntary contribution